Analisis Gaya Kepemimpinan Kepala Sekolah dan Kinerja Guru Pada SDN XYZ - Enitakarina Sinulingga; Nur Ahyani; Syaiful Eddy (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine and describe the partial and simultaneous influence of managerial competence and work discipline of school principals on teacher performance in state junior high schools in West Prabumulih District. The population in this study were all teachers at Public Middle Schools in West Prabumulih District, namely Public Middle School 4 and Public Middle School 9 in Prabumulih City, totaling 116 people and a total sample of 90 people. The sampling technique in this research is random. This research uses a descriptive analysis method and a quantitative approach. Data collection techniques use data using observation, questionnaires, and documentation analysis using t-test and F-test. The results of the research show that there is an influence of the principal's managerial competence on teacher performance in State Middle Schools in West Prabumulih District; the school principal's work discipline influences the performance of teachers in Public Middle Schools in West Prabumulih District; and the principal's managerial competence and principal's work discipline simultaneously influence teacher performance in State Middle Schools in West Prabumulih District by 82.6%. The remaining 17.4% is influenced by other variables not examined in this research. In conclusion, there is a partial and simultaneous influence of managerial competence and work discipline of school principals on teacher performance Keywords: Managerial Competence; Work Discipline; Teacher Performance.